Implementasi Kesesuaian Pencatatan Keuangan pada Pernyataan Standar Akuntansi Pemerintahan Nomor 05 - Luthfiana Ganie, Cindy; Wijayanti, Rahma Rina (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Financial information presented in trasparent and accountable and support the concept of good governance. Government Accounting Standards as the basis for reported of financial statements. Health facilities are on of those that need to be reviewed for implementation conformity the inventory accounting records based on Governement Accounting Standards Statement Number 05. The research method used is a qualitative data with interview as data collection technique and documentation of financial statements. The results of the study indicate that the conformity between inventory accounting report in health facilities x has been implemented well.